ANALYSIS OF FACTORS THAT INFLUENCE STUDENT ENTREPRENEURSHIP INTEREST IN THE DIGITAL ERA - Revansa, Marisa; Mardalis, Ahmad (Sekolah tinggi ilmu ekonomi pemuda, 2024)
The purpose of this study is to analyze the factors that influence student entrepreneurial interest in the digital era. This research method is quantitative. The type of data used in the research is primary data. The population of this study were students of the management study program at Muhammadiyah University of Surakarta. The sample technique used in this study was purposive sampling. The number of samples in this study were 234 respondents. The method used for data collection is the questionnaire method. The data analysis technique used in this research is SEM PLS using Smart PLS tools. The results of this study are Entrepreneurship education has a negative and insignificant effect on entrepreneurial interest in UMS Management students. Self-efficacy has a positive and significant influence on entrepreneurial interest in UMS Management students. Digital literacy has a negative and insignificant effect on entrepreneurial interest in UMS Management students. The family environment has a positive and significant influence on the entrepreneurial interest of UMS Management students. Motivation has a positive and significant influence on the entrepreneurial interest of UMS Management students.